IRON DEFICIENCY CONDITIONS IN PREGNANT WOMEN AND PUERPERAS - V. L. Tyutyunnik (Медицинский совет, 2017)
The frequency of iron-deficiency conditions (IDC) in pregnant women in the world ranges from 25 to 50% at the average. In developing countries, their prevalence ranges from 35 to 75%, and in developed ones amounts to 18-20%. According to the Ministry of Health of Russia, the average frequency of IDC in pregnant women in Russia ranges from 39 to 44%, and in postpartum women – from 24% to 27% [1–3].Iron deficiency (ID) adversely affects pregnancy, childbirth, postpartum period, fetus and newborn conditions, contributing to the increase in the frequency of threatened abortion, placental insufficiency, delayed growth and fetal hypoxia, premature birth, uterine inertia, frequency and volume of pathological blood loss in childbirth and the early postpartum period, infectious complications and hypogalactia in postpartum women. Iron supplementation to prevent reduces the risk of anemia in motherto-time delivery by 70% and iron-deficiency States by 57%.In the modern market of pharmaceutical industry the drug Sorbifer Durules has been well established (EGIS, Hungary). The use of this drug in a large sample of pregnant and postpartum women in recent years has proved its efficacy in the treatment of ID in this patient cohort.